Adhesive tape
A UV-curable adhesive tape with a 405 nm ultraviolet-cured layer addresses the issue of adhesive residue and peeling during high-temperature bonding by ensuring high gel fraction and tensile modulus, enabling easy removal and residue-free protection for semiconductor chips.
Patent Information
- Application Number
- JP2024163803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-25
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional adhesive tapes fail to withstand high-temperature thermocompression bonding processes (260°C) without shrinking, peeling off, and leaving adhesive residue due to high heat and pressure, especially when applied to uneven surfaces with semiconductor chips.
An adhesive tape with a UV-curable adhesive layer on a base film, cured by 405 nm ultraviolet rays at 3000 mJ/cm², achieving a gel fraction of 90% or more, tensile modulus of 1.0×10⁷ Pa at 270°C, and minimal weight loss, ensuring easy peeling without residue.
The adhesive tape provides effective protection and easy removal without adhesive residue even at high temperatures, maintaining integrity and preventing chemical adhesion during thermocompression bonding.
Smart Images

Figure 2024178319000001 
Figure 2024178319000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive tape. [Background technology]
[0002] In the manufacturing process of semiconductor chips, adhesive tapes are used to facilitate the handling of wafers and semiconductor chips during processing and to prevent breakage. For example, when a thick-film wafer cut from a high-purity silicon single crystal is ground to a predetermined thickness to produce a thin-film wafer, the grinding is performed after adhering an adhesive tape to the thick-film wafer.
[0003] The adhesive composition used in such a pressure-sensitive adhesive tape is required to have high enough adhesion to firmly fix adherends such as wafers and semiconductor chips during the processing step, and also to be able to peel the adherends such as wafers and semiconductor chips without damaging them after the processing step is completed (hereinafter, also referred to as "high adhesion and easy peeling"). As an adhesive composition that realizes high adhesion and easy peeling, Patent Document 1 discloses an adhesive tape that uses a photocurable adhesive that hardens and loses adhesive strength when irradiated with light such as ultraviolet light. By using a photocurable adhesive as the adhesive, the adherend can be reliably fixed during processing, and can be easily peeled off by irradiating with ultraviolet light or the like. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-32946 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, as semiconductor products become thinner and smaller, semiconductor devices are being manufactured in which many semiconductor chips are stacked on a wafer. In manufacturing such semiconductor devices in which many semiconductor chips are stacked, the semiconductor chips are fixed onto the wafer or semiconductor chips by a thermocompression bonding process while the wafer or semiconductor chips are protected by adhesive tape. The present inventors have found that, since the thermocompression bonding process requires a high temperature of 260°C, which is higher than the conventional high temperature process, even an adhesive tape using a conventional curable adhesive cannot withstand the heat of the high temperature process, and the base film of the adhesive tape shrinks, and the adhesive layer is pulled by the shrinkage, causing the adhesive tape to peel off. In addition, since the thermocompression bonding process requires pressure in addition to high temperature, the adhesive adhesion is easily promoted, and adhesive residue is easily generated. Furthermore, the wafer on which the thermocompression bonding process is performed often has bumps with large irregularities formed on the adhesive tape attachment surface, and if the adhesive gets caught in the deep part of the irregularities, it will tear off during peeling, leaving adhesive residue.
[0006] An object of the present invention is to provide an adhesive tape which protects an adherend even when used in a process involving high-temperature treatment up to 260°C, and which can be peeled off without leaving any adhesive residue. [Means for solving the problem]
[0007] The present invention relates to an adhesive tape having a base film and an ultraviolet-curable adhesive layer laminated on one side of the base film, the adhesive tape being irradiated with 405 nm ultraviolet light at 3000 mJ / cm on the surface of the base film side of the adhesive tape. 2 The gel fraction of the ultraviolet-curable adhesive layer after irradiation is 90% or more, and the 405 nm ultraviolet light is irradiated at 3000 mJ / cm on the surface of the base film side of the adhesive tape. 2 When the tensile modulus of the adhesive tape after irradiation at X°C is Et(X), the value of Et(270) is 1.0×10 7 It is an adhesive tape having a compressive strength of 100 Pa or more. The present invention will be described in detail below.
[0008] The pressure-sensitive adhesive tape of the present invention has an ultraviolet-curable pressure-sensitive adhesive layer laminated on one side of the above-mentioned base film. By having an ultraviolet-curable adhesive layer, the adhesive tape can be attached to an adherend with sufficient adhesive strength to protect the adherend, and by curing the ultraviolet-curable adhesive layer after attachment, the adherend can be protected even when a high-temperature treatment is performed. Furthermore, after protection is no longer required, the adhesive tape can be easily peeled off without leaving any adhesive residue.
[0009] The adhesive tape of the present invention is a tape that is irradiated with 405 nm ultraviolet light at 3000 mJ / cm on the surface of the base film side of the adhesive tape. 2 The gel fraction of the ultraviolet-curable adhesive layer after irradiation is 90% or more. By having a gel fraction of 90% or more in the ultraviolet-curable adhesive layer after ultraviolet irradiation, adhesion enhancement is unlikely to progress even at high temperatures, so that the adhesive tape can be peeled off without leaving any adhesive residue after protection is no longer necessary. In addition, the chemical resistance of the adhesive tape can also be improved. In addition, if the ultraviolet-curable adhesive layer can be cured by irradiating the surface on the base film side with ultraviolet rays, it becomes possible to cure the ultraviolet-curable adhesive layer after bonding the adhesive tape to the adherend. From the viewpoint of further improving the suppression of adhesion enhancement and the chemical resistance of the adhesive tape, the gel fraction of the ultraviolet-curable adhesive layer after ultraviolet irradiation is preferably 93% or more, more preferably 95% or more, and even more preferably 97% or more. The gel fraction of the ultraviolet-curable pressure-sensitive adhesive layer after irradiation with ultraviolet rays is usually 100% or less. In addition, when the pressure-sensitive adhesive tape of the present invention has a structure in which other layers, such as a pressure-sensitive adhesive layer, are laminated on the other side of the base film, the above-mentioned base film side refers to the side of the base film opposite to the side on which the ultraviolet-curable pressure-sensitive adhesive layer is laminated.
[0010] The adhesive tape of the present invention is characterized in that the 405 nm ultraviolet light is irradiated at 3000 mJ / cm on the surface of the base film side of the adhesive tape. 2When the tensile modulus of the adhesive tape after irradiation at X°C is Et(X), the value of Et(270) is 1.0×10 7 Pa or more. When the adhesive tape after ultraviolet irradiation has a tensile modulus in the above range at 270°C, the adhesive tape has excellent heat resistance, and even when subjected to high-temperature treatment up to 260°C, the adhesive tape is unlikely to soften or shrink, and unintended peeling of the adhesive tape can be suppressed. The preferable lower limit of Et(270) is 3.0×10 7 Pa, more preferably the lower limit is 5.0×10 7 Pa, and a more preferable lower limit is 1.0×10 8 The upper limit of the Et(270) is not particularly limited, but is preferably 1.0×10 Pa from the viewpoint of ease of handling the adhesive tape. 9 Pa is preferred. The tensile modulus of the pressure-sensitive adhesive tape can be measured by the following method. 405 nm ultraviolet light with an integrated intensity of 3000 mJ / cm 2 The ultraviolet-curable adhesive layer is irradiated from the surface of the substrate film side so that the ultraviolet-curable adhesive layer is cured. Next, a punching blade is used to punch out the long side so that the long side is the same as the flow direction during tape production, to prepare a 5 mm x 35 mm test piece. The obtained test piece is immersed in liquid nitrogen and cooled to -50°C, and then heated to 300°C under the conditions of 10°C / min and 10Hz frequency in a constant temperature rise tensile mode using a viscoelasticity spectrometer (DVA-200, manufactured by IT Measurement and Control Co., Ltd., or an equivalent product), and the tensile modulus is measured. The value of the tensile modulus (E') at a temperature of X°C at this time is Et(X). That is, the value of the tensile modulus (E') at a temperature of 270°C is Et(270).
[0011] The pressure-sensitive adhesive tape of the present invention preferably has a value of Et(270) / Et(200) of 0.1 or more. By reducing the difference between the tensile modulus of the adhesive tape at 270°C and the tensile modulus at 200°C after ultraviolet irradiation, the adhesive tape can have better heat resistance, and unintended peeling of the adhesive tape can be further suppressed. From the viewpoint of further suppressing the peeling, the value of Et(270) / Et(200) is more preferably 0.2 or more, even more preferably 0.3 or more, and particularly preferably 0.5 or more. There is no particular upper limit for the value of Et(270) / Et(200), and the closer to 1 the better, but it is usually 1 or less, and preferably less than 0.8.
[0012] The adhesive tape of the present invention is characterized in that the 405 nm ultraviolet light is irradiated at 3000 mJ / cm on the surface of the base film side of the adhesive tape. 2 After irradiation, the temperature is increased from 25° C. to 280° C. at a rate of 5° C. / min, and the weight loss rate when held for 10 minutes after the temperature increase is preferably 5% or less. The weight loss at a high temperature of 280°C is small, that is, the thermal decomposition at high temperatures is unlikely to occur, so that the amount of outgas generated by thermal decomposition is small, and peeling caused by outgas collected at the interface between the adherend and the pressure-sensitive adhesive tape can be prevented. From the viewpoint of preventing peeling at high temperatures, the weight loss rate is more preferably 4% or less, even more preferably 3% or less, and is usually 0% or more. The weight loss rate can be measured by the following method. 405 nm ultraviolet light with an integrated intensity of 3000 mJ / cm 2 The ultraviolet-curable adhesive layer is cured by irradiating the ultraviolet-curable adhesive layer from the surface of the substrate film side so that the ultraviolet-curable adhesive layer is cured. Next, the adhesive tape is punched into a circle of φ5 mm to prepare a measurement sample. The weight of the obtained measurement sample is measured, and measurement is performed using a differential thermal thermogravimetric simultaneous measurement device (TG-DTA; STA7200, manufactured by Hitachi High-Tech Science Corporation, or an equivalent product). The temperature is increased from 25°C to 280°C at a rate of 5°C / min, and the weight of the measurement sample is measured after being held at 280°C for 10 minutes. The weight loss rate can be calculated from the weight before and after heating.
[0013] The substrate film preferably has an ultraviolet ray transmittance of 1% or more at 405 nm. When the substrate film has a 405 nm ultraviolet transmittance of 1% or more, the ultraviolet curable adhesive layer can be cured through the substrate film, and the gel fraction of the ultraviolet curable adhesive layer after the ultraviolet irradiation can be easily adjusted. As a result, adhesive residue on the adherend due to enhanced adhesion can be suppressed. The ultraviolet transmittance is more preferably 10% or more, even more preferably 50% or more, and particularly preferably 70% or more. When the ultraviolet transmittance is equal to or more than these lower limits, the ultraviolet curable adhesive layer can be sufficiently cured without using a photosensitizer. The upper limit of the ultraviolet transmittance is not particularly limited, and the higher the better, and is usually 100% or less. The ultraviolet transmittance can be measured using a spectrophotometer (U-3900, manufactured by Hitachi, Ltd., or an equivalent product). More specifically, the transmittance at 405 nm can be measured by measuring in the range of 800 to 200 nm at a scan speed of 300 nm / min and a slit interval of 4 nm.
[0014] The above base film has a tensile modulus of elasticity of 5.0×10 at X°C, where Ef(X) is the tensile modulus of elasticity. 7 It is preferable that the pressure is 1 Pa or more. When the tensile modulus of elasticity at 270°C of the base film is within the above range, the adhesive tape can have better heat resistance, and peeling due to thermal shrinkage or softening of the base film during high-temperature treatment can be suppressed. A more preferable lower limit of the Ef(270) is 1.0 × 10 8 Pa, and a more preferable lower limit is 5.0×10 8 Pa, and the particularly preferred lower limit is 1.0×10 9 The upper limit of the Ef(270) is not particularly limited, but is preferably 1.0×10 Pa from the viewpoint of ease of handling the adhesive tape. 10 Pa is preferred. The tensile modulus of elasticity of the base film can be measured in the same manner as that of the pressure-sensitive adhesive tape.
[0015] The base film is not particularly limited as long as the resulting pressure-sensitive adhesive tape has a tensile modulus and gel fraction within the above-mentioned ranges. However, in order to achieve excellent heat resistance and strength, it is preferable that the base film contains a resin having at least one selected from the group consisting of amides, imides, ethers and ketones in the main chain skeleton of the repeating units. Examples of the resin having at least one selected from the group consisting of amide, imide, ether and ketone in the main chain skeleton of the repeating bond unit include polyamide, polyimide, polyether, polyketone, etc. Among them, the base film preferably contains a polyamide resin because of its superior heat resistance and strength, and more preferably contains a polyamide resin having a long-chain alkyl group or aromatic group having 4 to 12 carbon atoms in the main chain skeleton of the repeating unit because of its superior ultraviolet transmittance. Examples of the polyamide resin having a long-chain alkyl group or an aromatic group having 4 to 12 carbon atoms in the main chain skeleton of the repeating unit include nylon 9T and nylon 6T.
[0016] The thickness of the base film is not particularly limited, but the lower limit is preferably 25 μm, more preferably 50 μm, and the upper limit is preferably 250 μm, more preferably 125 μm. When the base film is in this range, a pressure-sensitive adhesive tape with excellent handleability can be obtained.
[0017] The adhesive constituting the ultraviolet-curable adhesive layer is not particularly limited as long as it is ultraviolet-curable, and examples thereof include ultraviolet-curable adhesives that contain a polymerizable polymer as the main component and an ultraviolet polymerization initiator as a polymerization initiator. Examples of the polymerizable polymer include (meth)acrylic polymers and urethane acrylate polymers. Among them, (meth)acrylic polymers are preferred because they are easy to satisfy the gel fraction and Et(270), and (meth)acrylic acid alkyl ester-based polymerizable polymers having radically polymerizable unsaturated bonds in the molecule are more preferred. The above-mentioned (meth)acrylic acid alkyl ester-based polymerizable polymer can be obtained, for example, by synthesizing a (meth)acrylic polymer having a functional group in the molecule in advance, and reacting it with a compound having a functional group reactive with the above-mentioned functional group and a radically polymerizable unsaturated bond in the molecule. Hereinafter, the "(meth)acrylic polymer having a functional group in the molecule" is referred to as the "functional group-containing (meth)acrylic polymer", and the "compound having a functional group reactive with the above-mentioned functional group and a radically polymerizable unsaturated bond in the molecule" is referred to as the "functional group-containing unsaturated compound".
[0018] The functional group-containing (meth)acrylic polymer is obtained by copolymerizing an acrylic acid alkyl ester and / or a methacrylic acid alkyl ester, the carbon number of which is usually in the range of 2 to 18, with a functional group-containing monomer and, if necessary, with other modifying monomers copolymerizable therewith, by a conventional method. The weight average molecular weight of the functional group-containing (meth)acrylic polymer is usually about 200,000 to 2,000,000. In this specification, the weight average molecular weight can usually be determined by a GPC method, for example, at 40°C, using THF as an eluent and HSPgel HR MB-M 6.0 x 150 mm (Waters) as a column, with polystyrene standards.
[0019] Examples of the functional group-containing monomer include a carboxy group-containing monomer, a hydroxyl group-containing monomer, an epoxy group-containing monomer, an isocyanate group-containing monomer, and an amino group-containing monomer. Examples of the carboxy group-containing monomer include acrylic acid and methacrylic acid. Examples of the hydroxyl group-containing monomer include hydroxyethyl acrylate and hydroxyethyl methacrylate. Examples of the epoxy group-containing monomer include glycidyl acrylate and glycidyl methacrylate. Examples of the isocyanate group-containing monomer include isocyanate ethyl acrylate and isocyanate ethyl methacrylate. Examples of the amino group-containing monomer include aminoethyl acrylate and aminoethyl methacrylate.
[0020] Examples of the other copolymerizable modifying monomers include various monomers used in general (meth)acrylic polymers, such as vinyl acetate, acrylonitrile, and styrene.
[0021] As the functional group-containing unsaturated compound to be reacted with the functional group-containing (meth)acrylic polymer, the same as the functional group-containing monomer described above can be used according to the functional group of the functional group-containing (meth)acrylic polymer. For example, when the functional group of the functional group-containing (meth)acrylic polymer is a carboxy group, an epoxy group-containing monomer or an isocyanate group-containing monomer is used. When the functional group is a hydroxyl group, an isocyanate group-containing monomer is used. When the functional group is an epoxy group, a carboxy group-containing monomer or an amide group-containing monomer such as acrylamide is used. When the functional group is an amino group, an epoxy group-containing monomer is used.
[0022] Examples of the ultraviolet polymerization initiator include those that are activated by irradiation with ultraviolet light having a wavelength of 200 to 410 nm. Examples of such ultraviolet polymerization initiators include acetophenone derivative compounds, benzoin ether compounds, ketal derivative compounds, phosphine oxide derivative compounds, bis(η5-cyclopentadienyl)titanocene derivative compounds, benzophenone, Michler's ketone, chlorothioxanthone, todecylthioxanthone, dimethylthioxanthone, diethylthioxanthone, α-hydroxycyclohexylphenyl ketone, and 2-hydroxymethylphenylpropane. Examples of the acetophenone derivative compounds include methoxyacetophenone. Examples of the benzoin ether compounds include benzoin propyl ether and benzoin isobutyl ether. Examples of the ketal derivative compounds include benzyl dimethyl ketal and acetophenone diethyl ketal. These ultraviolet polymerization initiators may be used alone or in combination of two or more.
[0023] The ultraviolet-curable pressure-sensitive adhesive layer preferably contains a radically polymerizable polyfunctional oligomer or monomer. When the ultraviolet-curable pressure-sensitive adhesive layer contains a radically polymerizable polyfunctional oligomer or monomer, ultraviolet curability is improved. The polyfunctional oligomer or monomer preferably has a weight average molecular weight of 10,000 or less, and more preferably has a weight average molecular weight of 5,000 or less and has 2 to 20 radically polymerizable unsaturated bonds in the molecule so that the ultraviolet-curable pressure-sensitive adhesive layer is efficiently three-dimensionally reticulated by irradiation with ultraviolet light. The weight average molecular weight can be determined, for example, by using a GPC measurement method.
[0024] Examples of the polyfunctional oligomer or monomer include trimethylolpropane triacrylate, tetramethylolmethane tetraacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol monohydroxypentaacrylate, dipentaerythritol hexaacrylate, and the above-mentioned methacrylates. Other examples include 1,4-butylene glycol diacrylate, 1,6-hexanediol diacrylate, polyethylene glycol diacrylate, commercially available oligoester acrylates, and the above-mentioned methacrylates. These polyfunctional oligomers or monomers may be used alone or in combination of two or more.
[0025] The ultraviolet-curable pressure-sensitive adhesive layer may contain a crosslinking agent for the purpose of increasing the cohesive strength of the ultraviolet-curable pressure-sensitive adhesive. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, metal chelate-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents are preferred because they further increase the cohesive force of the ultraviolet-curable pressure-sensitive adhesive.
[0026] The crosslinking agent is preferably contained in the pressure-sensitive adhesive layer in an amount of 0.1 to 20% by weight. By including the crosslinking agent in the above range, the ultraviolet-curable adhesive can be crosslinked appropriately to further increase the cohesive strength of the ultraviolet-curable adhesive while maintaining a high adhesive strength. From the viewpoint of further increasing the cohesive strength of the ultraviolet-curable adhesive while maintaining a high adhesive strength, the more preferred lower limit of the content of the crosslinking agent is 0.5% by weight, the even more preferred lower limit is 1.0% by weight, the more preferred upper limit is 15% by weight, and the even more preferred upper limit is 10% by weight.
[0027] The ultraviolet-curable pressure-sensitive adhesive layer preferably contains a silicone or a fluorine compound. By containing a silicone or fluorine compound in the ultraviolet-curable adhesive layer, the silicone or fluorine compound bleeds out at the interface between the ultraviolet-curable adhesive layer and the adherend, so that the adhesive tape can be easily peeled off without leaving any adhesive residue after the treatment is completed. Examples of the silicone or fluorine compound include silicone diacrylate and polymers having a fluoroalkyl group (e.g., (meth)acrylic copolymers having a structural unit derived from fluoroacrylate).
[0028] The silicone or fluorine compound preferably has a functional group capable of crosslinking with the polymerizable polymer. Since the silicone or fluorine compound has a functional group capable of crosslinking with the polymerizable polymer, the silicone or fluorine compound can chemically react with the polymerizable polymer by the application of a crosslinking agent or exposure to ultraviolet light to bond with the polymerizable polymer, thereby preventing contamination of the adherend caused by the silicone or fluorine compound adhering thereto. The functional group capable of crosslinking with the polymerizable polymer is appropriately selected according to the functional group contained in the polymerizable polymer, and examples thereof include a carboxyl group, a radically polymerizable unsaturated bond, a hydroxyl group, an amide group, an isocyanate group, and an epoxy group. Of these, a radically polymerizable unsaturated bond is preferred. By the silicone or fluorine compound having a radically polymerizable unsaturated bond as a functional group capable of crosslinking with the polymerizable polymer, the silicone or fluorine compound is chemically reacted with the polymerizable polymer by ultraviolet irradiation and is incorporated into the polymerizable polymer, so that contamination caused by the silicone or fluorine compound adhering to the adherend is further suppressed. The crosslinkable functionality of the silicone or fluorine compound is, for example, 2 to 6, preferably 2 to 4, and more preferably 2.
[0029] The functional group capable of crosslinking with the polymerizable polymer is appropriately determined depending on the functional group contained in the polymerizable polymer. For example, when the polymerizable polymer is a (meth)acrylic acid alkyl ester type having a radically polymerizable unsaturated bond in the molecule, it is preferable to select a functional group capable of crosslinking with the unsaturated bond. The functional group capable of crosslinking with the unsaturated bond is a functional group having an unsaturated double bond, and specifically, for example, a silicone or fluorine compound containing a vinyl group, a (meth)acrylic group, an allyl group, a maleimide group, or the like is selected.
[0030] The content of the silicone or fluorine compound in the ultraviolet-curable pressure-sensitive adhesive layer is preferably 2% by weight at the lower limit, more preferably 5% by weight at the lower limit, and even more preferably 10% by weight at the lower limit, and preferably 40% by weight at the upper limit, more preferably 35% by weight at the upper limit, and even more preferably 30% by weight at the upper limit. By ensuring that the content of the silicone or fluorine compound is within the above range, the amount of outgassing generated from the pressure-sensitive adhesive tape can be reduced, making it possible to provide a pressure-sensitive adhesive tape with even better heat resistance and adhesive transfer prevention performance.
[0031] The ultraviolet-curable pressure-sensitive adhesive layer preferably contains urethane acrylate. When the ultraviolet-curable pressure-sensitive adhesive layer contains urethane acrylate, the flexibility of the pressure-sensitive adhesive tape is improved, and the obtained pressure-sensitive adhesive tape can be made less likely to tear.
[0032] The content of the urethane acrylate in the ultraviolet curable adhesive layer is preferably 20% by weight, more preferably 15% by weight, and even more preferably 10% by weight. The content of the urethane acrylate in the above range can provide an adhesive tape with better heat resistance and adhesive residue suppression performance. The lower limit of the content of the urethane acrylate is not particularly limited, but is preferably 1% by weight from the viewpoint of making the adhesive tape less likely to tear and suppressing adhesive residue.
[0033] The total content of the silicone or fluorine compound and the urethane acrylate in the ultraviolet-curable pressure-sensitive adhesive layer is preferably 50% by weight or less. By setting the total content of the silicone or fluorine compound and the urethane acrylate within the above range, the amount of outgassing generated by thermal decomposition of these components can be suppressed, and therefore unintended peeling due to outgassing can be suppressed while improving heat resistance. From the viewpoint of further suppressing the peeling, the upper limit of the total content of the silicone or fluorine compound and the urethane acrylate is more preferably 40% by weight, and even more preferably 25% by weight.
[0034] The ultraviolet-curable pressure-sensitive adhesive layer preferably contains a filler. The ultraviolet-curable adhesive layer contains a filler, which improves the elastic modulus and thereby improves the heat resistance of the adhesive tape. Examples of the filler include silica, alumina, carbon black, calcium, boron, magnesium, zirconia, etc. Among these, silica is preferred because it further improves the heat resistance.
[0035] The average particle size of the filler is not particularly limited, but the lower limit is preferably 0.06 μm, the more preferable lower limit is 0.07 μm, the preferable upper limit is 2 μm, and the more preferable upper limit is 1 μm. By having the average particle size of the filler in the above range, the dispersibility in the ultraviolet-curable adhesive can be further improved.
[0036] The lower limit of the filler content in the ultraviolet-curable pressure-sensitive adhesive layer is preferably 1% by weight, more preferably 3% by weight, and the upper limit is preferably 18% by weight, more preferably 12% by weight. When the content of the filler is within the above range, a pressure-sensitive adhesive tape having superior heat resistance can be obtained.
[0037] The ultraviolet-curable pressure-sensitive adhesive layer preferably contains a gas generating agent that generates gas in response to a stimulus. Since the ultraviolet-curable adhesive layer contains a gas generating agent, a gas generating agent can be generated by applying a stimulus after the process is completed, which creates a gap between the adherend and the adhesive tape due to the gas, making it easier to peel off the adhesive tape. The gas generating agent is not particularly limited, but is preferably a gas generating agent that generates gas by light, since it can be used in a high-temperature treatment process. Among them, carboxylic acid compounds such as phenylacetic acid, diphenylacetic acid, and triphenylacetic acid, or salts thereof, and tetrazole compounds such as 1H-tetrazole, 5-phenyl-1H-tetrazole, and 5,5-azobis-1H-tetrazole, or salts thereof, are preferred, since they have excellent resistance to treatment involving heating. Such gas generating agents generate gas by irradiation with light such as ultraviolet light, while having high heat resistance that does not decompose even at high temperatures of about 260°C.
[0038] The ultraviolet-curable adhesive layer may contain a photosensitizer. By containing the photosensitizer, the ultraviolet-curable adhesive layer can be sufficiently cured even when the substrate film has a low ultraviolet transmittance at 405 nm. In addition, the photosensitizer has an effect of amplifying the stimulation of the gas-generating agent by light, so that the gas can be released by irradiation with less light. In addition, the gas can be released by light in a wider wavelength range. Examples of the photosensitizer include thioxanthone compounds such as 2,4-diethylthioxanthone, and anthracene compounds such as dibutylanthracene and dipropylanthracene. Other examples include 2,2-dimethoxy-1,2-diphenylethan-1-one, benzophenone, 2,4-dichlorobenzophenone, o-benzoyl methyl benzoate, 4,4'-bis(dimethylamino)benzophenone, and 4-benzoyl-4'methyldiphenyl sulfide. These photosensitizers may be used alone or in combination of two or more. The photosensitizers are thermally decomposed at high temperatures to generate outgassing and foam the ultraviolet-curable adhesive layer, so that using a large amount of them may cause adhesive residue or unintended peeling. Therefore, it is preferable to use as little of the photosensitizer as possible.
[0039] The ultraviolet-curable pressure-sensitive adhesive layer may contain known additives such as plasticizers, resins, surfactants, waxes, etc. These additives may be used alone or in combination.
[0040] The storage modulus G' of the ultraviolet-curable pressure-sensitive adhesive layer before ultraviolet irradiation is not particularly limited, but it is preferable that the storage modulus G' at 23° C. is 5.0×10 3 Pa or more, 1.0×10 5 It is preferable that the storage modulus G' of the ultraviolet-curable pressure-sensitive adhesive layer at 23°C before ultraviolet irradiation is in the above range, so that the adherend can be protected with sufficient adhesive strength. The storage modulus G' of the ultraviolet-curable pressure-sensitive adhesive layer at 23°C before ultraviolet irradiation can be adjusted by the type of pressure-sensitive adhesive constituting the ultraviolet-curable pressure-sensitive adhesive layer, the type and amount of filler, etc. The storage modulus G' of the above-mentioned ultraviolet-curable adhesive layer before ultraviolet irradiation at 23°C can be determined by measuring the storage modulus using a viscoelasticity spectrometer (e.g., DVA-200, manufactured by IT Measurement and Control Co., Ltd.) under conditions of a constant heating rate shear mode, a heating rate of 10°C / min, and a frequency of 10 Hz.
[0041] The thickness of the ultraviolet-curable adhesive layer is not particularly limited, but the lower limit is preferably 5 μm and the upper limit is preferably 100 μm. When the thickness of the ultraviolet-curable adhesive layer is within the above range, the adherend can be protected with sufficient adhesive strength, and adhesive residue upon peeling can also be suppressed. From the viewpoint of further improving the adhesive strength and further suppressing adhesive residue upon peeling, the more preferred lower limit of the thickness of the ultraviolet-curable adhesive layer is 10 μm, and the more preferred upper limit is 60 μm.
[0042] The pressure-sensitive adhesive tape of the present invention preferably has a pressure-sensitive adhesive layer on the surface of the base film opposite to the surface on which the ultraviolet-curable pressure-sensitive adhesive layer is laminated. Since the adhesive tape of the present invention is a double-sided adhesive tape having an ultraviolet-curable adhesive layer on one side of a base film and an adhesive layer on the other side, a support such as glass and an adherend can be adhered via the double-sided adhesive tape, making it possible to carry out a manufacturing process for a semiconductor device using the support.
[0043] The adhesive constituting the adhesive layer is not particularly limited, and examples thereof include acrylic adhesives, silicone adhesives, urethane adhesives, etc. Among these, acrylic and silicone adhesives are preferred because of their excellent heat resistance. In addition, the adhesive constituting the adhesive layer may be an ultraviolet-curable adhesive as described above. By using the ultraviolet-curable adhesive, the support can be held with sufficient adhesive strength, and when the support is a transparent support, the support can be held even when a high-temperature treatment is performed by curing the adhesive layer made of the ultraviolet-curable adhesive after pasting. In addition, the support can be easily removed after it is no longer needed.
[0044] The pressure-sensitive adhesive layer preferably contains a gas generating agent that generates gas in response to a stimulus. By including a gas generating agent in the pressure-sensitive adhesive layer, the support and the pressure-sensitive adhesive tape can be easily peeled off by applying a stimulus to generate gas after the end of the process. The gas generating agent can be the same as the gas generating agent for the ultraviolet-curable pressure-sensitive adhesive layer.
[0045] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but the lower limit is preferably 5 μm and the upper limit is preferably 30 μm. When the thickness of the pressure-sensitive adhesive layer is within the above range, the pressure-sensitive adhesive layer can be adhered to the support with sufficient adhesive strength. From the viewpoint of further increasing the adhesive strength to the support, the more preferred lower limit of the thickness of the pressure-sensitive adhesive layer is 10 μm and the more preferred upper limit is 20 μm.
[0046] The pressure-sensitive adhesive layer may contain known additives such as a photosensitizer, a plasticizer, a resin, a surfactant, a wax, a particulate filler, etc. These additives may be used alone or in combination.
[0047] The pressure-sensitive adhesive tape of the present invention may have an anchor layer between the substrate film and the ultraviolet-curable pressure-sensitive adhesive layer. When an anchor layer is provided between the substrate film and the ultraviolet-curable pressure-sensitive adhesive layer, if the ultraviolet-curable pressure-sensitive adhesive layer contains a silicone or a fluorine compound, the silicone or the fluorine compound can be prevented from bleeding out onto the substrate film side, causing the ultraviolet-curable pressure-sensitive adhesive layer to peel off from the substrate film.
[0048] Examples of the anchor layer include acrylic adhesives, urethane adhesives, etc. Among these, acrylic adhesives are preferred because of their excellent anchoring performance.
[0049] The anchor layer may contain, as necessary, known additives such as inorganic fillers, heat stabilizers, antioxidants, antistatic agents, plasticizers, resins, surfactants, waxes, etc. These additives may be used alone or in combination.
[0050] The thickness of the anchor layer is not particularly limited, but the preferred lower limit is 1 μm, and the preferred upper limit is 30 μm. When the thickness of the anchor layer is within this range, the anchor strength between the ultraviolet curable pressure-sensitive adhesive layer and the base film can be further improved. From the viewpoint of further improving the anchor strength between the ultraviolet curable pressure-sensitive adhesive layer and the base film, the more preferred lower limit of the thickness of the anchor layer is 3 μm, and the more preferred upper limit is 10 μm.
[0051] The method for producing the adhesive tape of the present invention is not particularly limited, and a conventionally known method can be used. For example, the adhesive tape of the present invention can be produced by coating a solution of the ultraviolet-curable adhesive component on a film that has been subjected to a release treatment, drying the solution to form an ultraviolet-curable adhesive layer, and laminating the layer to a substrate film. In addition, when the adhesive tape of the present invention has the adhesive layer, the adhesive layer can be produced by using a solution of the adhesive constituting the adhesive layer to form an adhesive layer in the same manner as the ultraviolet-curable adhesive layer, and laminating the layer to the surface of the substrate film opposite to the surface to which the ultraviolet-curable adhesive layer is laminated.
[0052] The uses of the adhesive tape of the present invention are not particularly limited, but since the adhesive tape can protect the adherend and be peeled off without leaving any adhesive residue even when used in harsh environments such as high temperatures and pressure, it can be particularly suitably used as a protective tape for protecting wafers, semiconductor chips, etc. in the manufacture of electronic components. An example of a method for producing such electronic components is the following method, which includes, in this order, a substrate attachment step of attaching the pressure-sensitive adhesive tape of the present invention to a substrate via an ultraviolet-curable pressure-sensitive adhesive layer, a curing step of curing the ultraviolet-curable pressure-sensitive adhesive layer by irradiating ultraviolet light, a heat treatment step of treating the substrate at a high temperature of 260° C. or higher, and a peeling step of peeling the substrate from the pressure-sensitive adhesive tape of the present invention. Also, the following method for producing electronic components using an adhesive tape having an adhesive layer on the surface opposite to the surface on which the ultraviolet-curable adhesive layer of the substrate film is laminated, which is one embodiment of the present invention, can be mentioned. That is, the method includes, in this order, a substrate attachment step of attaching the adhesive tape to the substrate from the ultraviolet-curable adhesive layer, a support attachment step of attaching a support onto the adhesive layer, a curing step of curing the ultraviolet-curable adhesive layer by irradiating ultraviolet light, a heat treatment step of treating the substrate at a high temperature of 260°C or higher, and a peeling step of peeling the substrate from the adhesive tape. Also, the method includes, in this order, a substrate attachment step of attaching the adhesive tape to the substrate from the ultraviolet-curable adhesive layer, a curing step of curing the ultraviolet-curable adhesive layer by irradiating ultraviolet light, a support attachment step of attaching a support onto the adhesive layer, a heat treatment step of treating the substrate at a high temperature of 260°C or higher, and a peeling step of peeling the substrate from the adhesive tape.
[0053] The substrate is not particularly limited, and examples thereof include a silicon wafer, a semiconductor wafer, and a semiconductor chip. The support is not particularly limited, and examples thereof include glass, a polyimide film, and a glass epoxy substrate. The upper limit of the temperature in the heat treatment step at a high temperature of 260°C or higher is not particularly limited, and is, for example, 400°C, and preferably 300°C. The heat treatment process at a high temperature of 260° C. or higher is not particularly limited, and examples thereof include a substrate manufacturing process, a chip mounting process, a thermocompression bonding process, a reflow process, etc. More specifically, examples thereof include a thermocompression bonding process or a reflow process in which an adhesive tape is heated to 260° C. or higher for several tens of seconds to about one minute. Effect of the Invention
[0054] According to the present invention, it is possible to provide an adhesive tape which protects an adherend even when used in a process involving high-temperature treatment that reaches 260° C., and which can be peeled off without leaving any adhesive residue. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0056] Example 1 (Manufacture of UV-curable adhesive A) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared, and 94 parts by weight of 2-ethylhexyl acrylate as an alkyl (meth)acrylate ester, 6 parts by weight of hydroxyethyl methacrylate as a functional group-containing monomer, 0.01 parts by weight of lauryl mercaptan, and 80 parts by weight of ethyl acetate were added to the reactor, and the reactor was heated to start reflux. Next, 0.01 parts by weight of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to start polymerization under reflux. Next, 0.01 parts by weight of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added 1 hour and 2 hours after the start of polymerization, and 0.05 parts by weight of t-hexylperoxypivalate was added 4 hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution of a functional group-containing (meth)acrylic polymer having a solid content of 55% by weight and a weight average molecular weight of 600,000 was obtained. To 100 parts by weight of the resin solid content of the obtained ethyl acetate solution containing the functional group-containing (meth)acrylic polymer, 3.5 parts by weight of 2-isocyanatoethyl methacrylate was added as a functional group-containing unsaturated compound and reacted to obtain a polymerizable polymer (acrylic polymer) A. Then, to 100 parts by weight of the resin solid content of the obtained ethyl acetate solution of the acrylic polymer A, 20 parts by weight of a release agent (silicone), 3 parts by weight of a filler, 10 parts by weight of a urethane acrylate, 0.2 parts by weight of a crosslinking agent, and 1 part by weight of a photopolymerization initiator were mixed to obtain an ethyl acetate solution of an ultraviolet-curing pressure-sensitive adhesive A. The release agent (silicone), filler, urethane acrylate, crosslinking agent, and photopolymerization initiator used were as follows. Release agent (silicone): Silicone diacrylate, EBECRYL 350, Daicel Allnex, weight average molecular weight 1000 Filler: Silica filler, Leolosil MT-10, manufactured by Tokuyama Corporation Urethane acrylate: UN-5500, manufactured by Negami Chemical Industries, Ltd. Crosslinking agent: Isocyanate-based crosslinking agent, Coronate L, manufactured by Nippon Urethane Industry Co., Ltd. Photopolymerization initiator: Esacure One, manufactured by Nippon SiberHegner Co., Ltd.
[0057] (Production of Adhesive A for Adhesive Layer) 100 parts by weight of the resin solid content of the ethyl acetate solution of the acrylic polymer A obtained in the production of the ultraviolet curing adhesive A was mixed with 10 parts by weight of the release agent (silicone), 12 parts by weight of the filler, 20 parts by weight of the urethane acrylate, 1.2 parts by weight of the crosslinking agent, 1 part by weight of the photopolymerization initiator, and 10 parts by weight of the gas generating agent to obtain an ethyl acetate solution of the adhesive A for the adhesive layer. The release agent (silicone), filler, urethane acrylate, crosslinking agent, and photopolymerization initiator were the same as those used in the production of the ultraviolet curing adhesive. The gas generating agent was a salt of a bistetrazole compound represented by the following formula (A).
[0058] [ka]
[0059] (Manufacture of adhesive for anchor layer) 100 parts by weight of the resin solid content of the ethyl acetate solution of the acrylic polymer was mixed with 12 parts by weight of the filler and 5 parts by weight of the crosslinking agent to obtain an ethyl acetate solution of the adhesive for the anchor layer. The following acrylic polymer, filler, and crosslinking agent were used. Acrylic polymer: SK Dyne 1604N, manufactured by Soken Chemical Industries, Ltd. Filler: Silica filler, Leolosil MT-10, manufactured by Tokuyama Corporation Crosslinking agent: Isocyanate-based crosslinking agent, Coronate L, manufactured by Nippon Urethane Industry Co., Ltd.
[0060] (Adhesive tape manufacturing) The obtained ethyl acetate solution of ultraviolet-curable adhesive A was coated on a release-treated surface of a 50 μm-thick polyethylene terephthalate (PET) film so that the adhesive layer would have a thickness of 130 μm after drying, and then dried at 100° C. for 10 minutes to form an ultraviolet-curable adhesive layer. Meanwhile, the obtained ethyl acetate solution of adhesive A for the adhesive layer was coated on the release-treated surface of another PET film having a thickness of 50 μm so that the adhesive layer would have a thickness of 20 μm after drying, and then dried at 110° C. for 5 minutes to form an adhesive layer. Furthermore, the obtained ethyl acetate solution of the adhesive for the anchor layer was coated on the release-treated surface of another PET film having a thickness of 50 μm so that the adhesive layer would have a thickness of 10 μm after drying, and then dried at 110° C. for 5 minutes to form an anchor layer. Next, a film (nylon 9T film) made of nylon 9T (Uniamide, manufactured by Unitika Co., Ltd.) having a thickness of 25 μm and having been subjected to corona treatment on both sides was prepared as a base film, the anchor layer prepared was laminated on one side of the nylon 9T film, and the PET film was peeled off to form an anchor layer on the base film. Thereafter, the obtained ultraviolet-curing adhesive layer was bonded to the surface of the nylon 9T film on which the anchor layer was formed, and the obtained adhesive layer was bonded to the surface of the nylon 9T film opposite to the surface on which the anchor layer was formed, to obtain an adhesive tape having a structure of ultraviolet-curing adhesive layer / anchor layer / base film / adhesive layer.
[0061] (Measurement of UV transmittance of substrate film) The transmittance of the substrate film to ultraviolet light at 405 nm was measured using a spectrophotometer (U-3900, manufactured by Hitachi, Ltd.).
[0062] (Measurement of Ef(270)) The substrate film was punched out with a punch blade into a size of 5 x 35 mm with the long side aligned with the flow direction during the production of the substrate film, to obtain a measurement sample. The obtained measurement sample was immersed in liquid nitrogen to cool to -50°C, and then the tensile modulus of the substrate film at 270°C was measured using a viscoelasticity spectrometer (DVA-200, manufactured by IT Measurement & Control Co., Ltd.) under the conditions of a constant temperature rise tensile mode, a temperature rise rate of 10°C / min, and a frequency of 10 Hz.
[0063] (Measurement of storage modulus G' before UV irradiation) The storage modulus of the ultraviolet-curable adhesive layer was measured using a viscoelasticity spectrometer (DVA-200, IT Measurement and Control Co., Ltd.) under conditions of a constant heating rate shear mode, a heating rate of 10°C / min, and a frequency of 10 Hz, and the storage modulus G' of the ultraviolet-curable adhesive layer at 23°C before ultraviolet irradiation was determined.
[0064] (Measurement of gel fraction after UV irradiation) Using a high-pressure mercury ultraviolet irradiator, ultraviolet rays of 405 nm were irradiated from the base film side of the adhesive tape to the adhesive tape surface, with an integrated intensity of 3000 mJ / cm 2 The ultraviolet-curable adhesive layer was crosslinked and cured by irradiating the adhesive so that the ultraviolet-curable adhesive layer was crosslinked and cured. Next, 0.1 g of only the cured ultraviolet-curable adhesive layer was scraped off and immersed in 50 ml of ethyl acetate, and shaken for 24 hours with a shaker at a temperature of 23°C and 120 rpm (hereinafter, the scraped ultraviolet-curable adhesive layer is referred to as the adhesive composition). After shaking, ethyl acetate and the adhesive composition that absorbed the ethyl acetate and swelled were separated using a metal mesh (opening #200 mesh). The separated adhesive composition was dried for 1 hour under the condition of 110°C. The weight of the adhesive composition including the dried metal mesh was measured, and the gel fraction after ultraviolet irradiation was calculated using the following formula. Gel fraction (%) = 100 × (W 1 -W 2 ) / W 0 (W 0 : initial adhesive composition weight, W 1 : Weight of the adhesive composition including the metal mesh after drying, W2 (initial weight of metal mesh)
[0065] (Measurement of Et(270)) Using a high-pressure mercury ultraviolet irradiator, ultraviolet rays of 405 nm were irradiated from the base film side of the adhesive tape to the adhesive tape surface, with an integrated intensity of 3000 mJ / cm 2 The ultraviolet-curable adhesive layer was crosslinked and cured. Next, a punching blade was used to punch out the long side so that it was the same as the flow direction during the production of the adhesive tape, to prepare a test piece of 5 mm x 35 mm. The obtained test piece was immersed in liquid nitrogen and cooled to -50°C, and then heated to 300°C using a viscoelasticity spectrometer (DVA-200, manufactured by IT Measurement and Control Co., Ltd.) under the conditions of a constant-rate heating tensile mode, a heating rate of 10°C / min, and a frequency of 10 Hz, to measure the tensile modulus. The value of the tensile modulus (E') at a temperature of X°C at this time was taken as Et(X). That is, the value of the tensile modulus (E') at a temperature of 270°C was taken as Et(270).
[0066] (Calculation of Et(270) / Et(200)) The tensile modulus (Et(200)) of the obtained pressure-sensitive adhesive tape at 200°C was measured in the same manner as for Et(270). Et(270) / Et(200) was calculated from the obtained results of Et(270) and Et(200).
[0067] (Weight loss rate measurement) Using a high-pressure mercury ultraviolet irradiator, ultraviolet rays of 405 nm were irradiated from the base film side of the adhesive tape to the adhesive tape surface, with an integrated intensity of 3000 mJ / cm 2 The ultraviolet-curable adhesive layer was crosslinked and cured. The adhesive tape was then punched into a circle with a diameter of 5 mm to obtain a measurement sample. The weight of the obtained measurement sample was measured, and the weight loss amount was measured when the temperature was raised from 25°C to 280°C at a heating rate of 5°C / min and then held for 10 minutes using a differential thermal and thermogravimetric simultaneous analyzer (TG-DTA; STA7200, Hitachi High-Tech Science Corporation). The weight loss rate was calculated from the weight before and after heating.
[0068] (Examples 2 to 10, Comparative Examples 1 to 4) An adhesive tape was obtained and each measurement was carried out in the same manner as in Example 1, except that the material and thickness of the base film and the composition of the ultraviolet-curable adhesive layer were changed as shown in Table 1. Details of each material are shown below. In Example 5, ultraviolet-curable adhesive B shown below was used. (1) Material of the base film Expeak: Aromatic polyether ether ketone, manufactured by Kurabo Upilex: Copolymer of biphenyltetracarboxylic dianhydride and p-phenylenediamine, manufactured by Ube Industries Torsena: Special polyester, manufactured by Kurabo Kapton: Copolymer of pyromellitic anhydride and diaminodiphenyl ether, manufactured by Toray DuPont
[0069] (2) UV-curable adhesive B (Manufacture of UV-curable adhesive B) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared, and 94 parts by weight of 2-ethylhexyl acrylate as an alkyl (meth)acrylate ester, 6 parts by weight of hydroxyethyl methacrylate as a functional group-containing monomer, 0.01 parts by weight of lauryl mercaptan, and 80 parts by weight of ethyl acetate were added to the reactor, and the reactor was heated to start reflux. Next, 0.01 parts by weight of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to start polymerization under reflux. Next, 0.01 parts by weight of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added 1 hour and 2 hours after the start of polymerization, and 0.05 parts by weight of t-hexylperoxypivalate was added 4 hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution of a functional group-containing (meth)acrylic polymer having a solid content of 55% by weight and a weight average molecular weight of 600,000 was obtained. To 100 parts by weight of the resin solid content of the obtained ethyl acetate solution containing the functional group-containing (meth)acrylic polymer, 1.0 part by weight of 2-isocyanatoethyl methacrylate was added as a functional group-containing unsaturated compound and reacted to obtain a polymerizable polymer (acrylic polymer) B. Then, to 100 parts by weight of the resin solid content of the obtained ethyl acetate solution of the acrylic polymer B, 20 parts by weight of a release agent (silicone), 3 parts by weight of a filler, 10 parts by weight of a urethane acrylate, 0.2 parts by weight of a crosslinking agent, and 1 part by weight of a photopolymerization initiator were mixed to obtain an ethyl acetate solution of an ultraviolet-curing adhesive B. The release agent (silicone), filler, urethane acrylate, crosslinking agent, and photopolymerization initiator were the same types as those of the ultraviolet-curing adhesive A.
[0070] (3)Other Photosensitizer: KAYACURE DETX-S, manufactured by Nippon Kayaku Co., Ltd.
[0071] <Evaluation> The pressure-sensitive adhesive tapes obtained in the Examples and Comparative Examples were evaluated by the following methods. The results are shown in Table 1.
[0072] (Evaluation of heat resistance) The ultraviolet-curable adhesive layer side of the adhesive tape cut into a circle with a diameter of 20 cm was attached to a silicon wafer with a diameter of 20 cm and a thickness of about 750 μm. Next, the adhesive layer side of the adhesive tape was attached to a glass wafer (Tempax, manufactured by SCHOTT) with a diameter of 20 cm and a thickness of 0.6 mm. After attachment, ultraviolet light with a wavelength of 405 nm was irradiated from the glass wafer side to the ultraviolet-curable adhesive layer with an integrated intensity of 3000 mJ / cm, with wavelengths of 365 nm or less cut off by a filter. 2 The ultraviolet-curable adhesive layer and the adhesive layer were crosslinked and cured. The obtained laminate of silicon wafer / adhesive tape / glass wafer was placed on a hot plate (NINOS ND-3H, manufactured by AZONE) set at 280° C. with the silicon wafer side facing down, and the time until peeling of the adhesive tape occurred was measured.
[0073] (Evaluation of peelability) The ultraviolet-curing adhesive layer side of the adhesive tape was attached to a silicon wafer having a diameter of 20 cm and a thickness of about 750 μm, and the adhesive layer side was then attached to a glass wafer having a diameter of 20 cm and a thickness of 0.6 mm to obtain a laminate. Next, a high-pressure mercury ultraviolet irradiator was used to irradiate the adhesive tape surface with 405 nm ultraviolet light at an irradiation intensity of 100 mW / cm. 2 The illuminance was adjusted so that the ultraviolet-curable adhesive layer and the adhesive layer were crosslinked and cured by irradiating the glass wafer side with light for 30 seconds. Thereafter, the laminate was placed on a hot plate set at 280° C. with the silicon wafer side facing down, and heat-treated for 10 minutes, and then allowed to cool. After cooling, the adhesive tape was peeled off from the silicon wafer. The peelability was evaluated as "○" if the adhesive tape could be easily peeled off, and "×" if it could not be peeled off. If the adhesive tape peeled off within 10 minutes, the heat treatment was stopped at the peeling stage, and the adhesive tape was left to cool before the peelability was evaluated.
[0074] (Evaluation of glue residue) To evaluate peelability, the silicon wafer after peeling off the adhesive tape was observed under an optical microscope. If the area of residual glue was less than 5% of the entire silicon wafer, it was marked as "◎", if it was 5% or more but less than 20%, it was marked as "○", if it was 20% or more but less than 50%, it was marked as "△", and if it was 50% or more, it was marked as "X".
[0075] (Evaluation of peelability during thermocompression bonding) The ultraviolet-curing adhesive layer side of the adhesive tape cut into a circle with a diameter of 20 cm was attached to the bumped surface of a 20 cm diameter, 50 μm thick silicon wafer (bump diameter φ=20 μm, distance between bumps 30 μm, bump height 45 μm). Next, the adhesive layer side of the adhesive tape was attached to a 20 cm diameter, 0.6 mm thick glass wafer (Tempax, manufactured by SCHOTT). After attachment, ultraviolet light with a wavelength of 405 nm was irradiated from the glass wafer side with an integrated intensity of 3000 mJ / cm2 onto the ultraviolet-curing adhesive layer, with wavelengths of 365 nm or less cut off by a filter. 2The obtained laminate of silicon wafer / adhesive tape / glass wafer was placed in an oven set at 200° C. with the glass wafer side facing down for 1 hour, and subjected to a heat treatment. After the heat treatment, a single crystal silicon thin wafer chip with a thickness of 50 μm was laminated on the silicon wafer of the laminate that had returned to room temperature using a flip chip bonder (FC6000, manufactured by Shibaura Mechatronics Co., Ltd.). Specifically, the laminate was adsorbed onto a SUS stage set at 80°C with the silicon wafer surface facing up, and a single crystal silicon thin wafer chip (9.8 mm x 9.8 mm, thickness 50 μm, surface roughness less than 0.1 μm, with a bonding film with a thickness of 25 μm) was laminated using a ceramic tool with a head size of 10 mm x 10 mm. The head temperature during lamination was 280°C, the pressure was 300 N, and the lamination time was 90 seconds. After laminating the single crystal silicon thin wafer chip, the adhesive tape was peeled off from the silicon wafer. The peelability during thermocompression bonding was evaluated as "○" if the adhesive tape could be easily peeled off and "×" if it could not be peeled off.
[0076] (Evaluation of adhesive residue during thermocompression) To evaluate the peelability during thermocompression bonding, the silicon wafer after peeling off the adhesive tape was observed under an optical microscope. The adhesive residue during thermocompression bonding was evaluated as follows: if 5% or less of the bumps in a 500μm square area had adhesive residue, it was marked as "◎", if more than 5% but less than 20% had adhesive residue, it was marked as "〇", if more than 20% but less than 50% had adhesive residue, it was marked as "△", and if more than 50% had adhesive residue, it was marked as "×".
[0077] [Table 1] [Industrial Applicability]
[0078] According to the present invention, it is possible to provide an adhesive tape which protects an adherend even when used in a process involving high-temperature treatment that reaches 260° C., and which can be peeled off without leaving any adhesive residue.
Claims
1. An adhesive tape having a base film and an ultraviolet-curable adhesive layer laminated on one side of the base film, The surface of the base film side of the adhesive tape is irradiated with 405 nm ultraviolet light at 3000 mJ / cm 2 the gel fraction of the ultraviolet-curable adhesive layer after irradiation is 90% or more; The 405 nm ultraviolet light was irradiated on the surface of the base film side of the adhesive tape at 3000 mJ / cm 2 When the tensile modulus of the adhesive tape after irradiation at X°C is Et(X), the value of Et(270) is 1.0 x 10 7 An adhesive tape having a compressive strength of 100 Pa or more.
2. The pressure-sensitive adhesive tape according to claim 1 , wherein the substrate film has an ultraviolet ray transmittance of 1% or more at 405 nm.
3. 3. The pressure-sensitive adhesive tape according to claim 1, wherein the value of Et(270) / Et(200) is 0.1 or more.
4. When the tensile modulus of the base film at X° C. is Ef(X), the value of Ef(270) is 5.0×10 7 The pressure-sensitive adhesive tape according to claim 1 , 2 or 3 , having a modulus of elasticity of 1 Pa or more.
5. The 405 nm ultraviolet light was irradiated on the surface of the base film side of the adhesive tape at 3000 mJ / cm 2 5. The pressure-sensitive adhesive tape according to claim 1, which, after irradiation, has a weight loss of 5% or less when heated from 25° C. to 280° C. at a rate of 5° C. / min and held for 10 minutes after heating.
6. 6. The pressure-sensitive adhesive tape according to claim 1, wherein the base film contains a resin having at least one selected from the group consisting of amides, imides, ethers and ketones in the main chain skeleton of repeating units.
7. 7. The pressure-sensitive adhesive tape according to claim 1, 2, 3, 4, 5 or 6, wherein the base film contains a polyamide resin having a long-chain alkyl group having 4 to 12 carbon atoms or an aromatic group in the main chain skeleton of the repeating unit.
8. 8. The adhesive tape according to claim 1, 2, 3, 4, 5, 6 or 7, wherein the ultraviolet-curable adhesive layer comprises a (meth)acrylic acid alkyl ester-based polymerizable polymer having a radically polymerizable unsaturated bond in the molecule, a polymerization initiator, and a silicone or fluorine compound having a functional group capable of crosslinking with the polymerizable polymer.
9. 9. The adhesive tape according to claim 1, further comprising an adhesive layer on the surface of said base film opposite to the surface on which said ultraviolet-curable adhesive layer is laminated.
10. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, which is used for producing electronic components.
Citation Information
Patent Citations
Releasable tacky adhesive polymer
JP1993032946A
